Panduan Identifikasi Plankton di Laboratorium: Penelitian - Alianto Alianto; Vera Sabariah; Tresia Sonya Tururaja; Sadida Anindya Bahtiar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
After knowing how to take and handle plankton water samples and knowing and understanding how to use a microscope, the next problem that arises is how to count or observe and identify plankton water samples with a microscope in the laboratory. Based on this, this community service aims to describe in detail how to identify plankton in the laboratory. The tools and materials used for plankton identification in the laboratory consist of a reversible microscope, preparations, Sedwig rafter cells, coverglass, dropper pipettes, counters, plankton water sample bottles, spray bottles, notebooks or HVS paper, 2B pencils, erasers and tissues. The stages of plankton identification in the laboratory consist of the preparation stage and the implementation stage. The preparation stage consists of preparations outside the laboratory and in the laboratory. Preparations outside the laboratory include plankton water sample bottles, spray bottles, counters, notebooks or HVS paper, 2B pencils, erasers and tissues. The most important preparation outside the laboratory is to prepare plankton identification sheets and plankton identification books. Preparations in the laboratory include a reciprocating microscope, preparations or SRC, dropper pipettes, and coverglass. The implementation stage of plankton identification in the laboratory consists of 18 procedures that must be followed sequentially. Plankton identification includes 18 procedures with a primary focus on sample loading, microscope setup, determination methods, and plankton counts.